Neuromuscular response differences to power vs strength back squat exercise in elite athletes. Issue 5 (4th July 2014) - Brandon, R.; Howatson, G.; Strachan, F.; Hunter, A. M.
Abstract : The study's aim was to establish the neuromuscular responses in elite athletes during and following maximal 'explosive' regular back squat exercise at heavy, moderate, and light loads. Ten elite track and field athletes completed 10 sets of five maximal squat repetitions on three separate days. Knee extension maximal isometric voluntary contraction (MIVC), rate of force development (RFD) and evoked peak twitch force (Pt) assessments were made pre‐ and post‐session. Surface electromyography [root mean square (RMS)] and mechanical measurements were recorded during repetitions. The heavy session resulted in the greatest repetition impulse in comparison to moderate and light sessions ( P  < 0.001), while the latter showed highest repetition power ( P  < 0.001). MIVC, RFD, and Pt were significantly reduced post‐session ( P  < 0.01), with greatest reduction observed after the heavy, followed by the moderate and light sessions accordingly. Power significantly reduced during the heavy session only ( P  < 0.001), and greater increases in RMS occurred during heavy session ( P  < 0.001), followed by moderate, with no change during light session. In conclusion, this study has shown in elite athletes that the moderate load is optimal for providing a neuromuscular stimulus but with limited fatigue. This type of intervention could be potentially used in the development of both strength and power in elite athletic populations.